2013
DOI: 10.1021/nn3055175
|View full text |Cite
|
Sign up to set email alerts
|

Single-Walled Carbon Nanotube Surface Control of Complement Recognition and Activation

Abstract: Carbon nanotubes (CNTs) are receiving considerable attention in site-specific drug and nucleic acid delivery, photodynamic therapy, and photoacoustic molecular imaging. Despite these advances, nanotubes may activate the complement system (an integral part of innate immunity), which can induce clinically significant anaphylaxis. We demonstrate that single-walled CNTs coated with human serum albumin activate the complement system through C1q-mediated classical and the alternative pathways. Surface coating with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
120
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(123 citation statements)
references
References 64 publications
3
120
0
Order By: Relevance
“…Similar observations have been reported with carbon nanotubes coated with PEG-conjugated molecules or covalently functionalized with PEG, where gross surface polymer architectural changes not only triggered lectin pathway, but further modulated the mode of lectin pathway activation through binding of different lectin pathway initiating molecules (e.g., MBL vs. L-ficolin) (13).…”
Section: Examples Of Nanoparticle-mediated Activation Of Lectin Pathwaysupporting
confidence: 84%
See 2 more Smart Citations
“…Similar observations have been reported with carbon nanotubes coated with PEG-conjugated molecules or covalently functionalized with PEG, where gross surface polymer architectural changes not only triggered lectin pathway, but further modulated the mode of lectin pathway activation through binding of different lectin pathway initiating molecules (e.g., MBL vs. L-ficolin) (13).…”
Section: Examples Of Nanoparticle-mediated Activation Of Lectin Pathwaysupporting
confidence: 84%
“…Although long believed that such strategies could suppress opsonization events in the blood (33,34), recent studies have demonstrated that some of these engineered entities can, indeed, incite complement and depending on surface polymer configuration complement activation may proceed exclusively through the lectin pathway (12,13,(17)(18)(19)21). For example, alteration of poloxamine 908 copolymer architecture on polystyrene nanospheres of 220 nm in size from a flat to mushroombrush configuration switched complement activation from the C1q-dependent classical pathway to a lectin pathway in human serum (12).…”
Section: Examples Of Nanoparticle-mediated Activation Of Lectin Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…53,60,61 In terms of bacterial or viral presence, the complement system recognizes these infective entities through pattern recognition. A similar mechanism is thought to Fig.…”
Section: Complement and Molecular Recognitionmentioning
confidence: 99%
“…There are 2 main kinds of CNTs: single-wall CNTs (SWCNTs) and multi-wall CNTs. Studies have found that CNTs have a unique feature defined as a transmembrane, which enables them to pass through various cell membranes passively (Andersen et al, 2013). However, CNTs are highly hydrophobic, are insoluble in both water and organic solvents, and their biocompatibility is very poor.…”
Section: Introductionmentioning
confidence: 99%